Dipole-induced Ohmic contacts between monolayer Janus MoSSe and bulk metals - Ning Zhao (Nature Portfolio, 2021)
Abstract Utilizing a two-dimensional material in an electronic device as channel layer inevitably involves the formation of contacts with metallic electrodes. As these contacts can dramatically affect the behavior of the device, we study the electronic properties of monolayer Janus MoSSe in contact with different metallic electrodes by first-principles calculations, focusing on the differences in the characteristics of contacts with the two sides of MoSSe. In particular, we demonstrate that the Fermi level pinning is different for the two sides of MoSSe, with the magnitude resembling that of MoS2 or MoSe2, while both sides can form Ohmic contacts with common electrode materials without any further adaptation, which is an outstanding advantage over MoS2 and MoSe2.